Cannabis use in cancer patients: acute and sustained associations with pain, cognition, and quality of life - Gregory Giordano; Renée Martin-Willett; Laurel P. Gibson; D. Ross Camidge; Daniel W. Bowles; Kent E. Hutchison; Angela D. Bryan (Open Exploration Publishing Inc., 2023)
Aim: Given the myriad of negative sequalae associated with cancer and its treatment, the palliative use of cannabis by cancer patients is increasingly of special interest. This research sought to explore associations of acute and sustained use of legal market edible cannabis products on pain, cognition, and quality of life in a group of cancer patients. Methods: In this observational study, cancer patients completed a baseline appointment, a two-week ad libitum cannabis use period, and an acute administration appointment that included assessments before cannabis use, one-hour post-use, and two-hour post-use. Participants completed self-report questionnaires related to the primary outcomes and the Stroop task as a measure of objective cognitive function. Results: Twenty-five participants [mean (standard deviation, SD) age = 54.3 years (15.6); 13 females (52.0%)] completed all study appointments and were included in the analysis. Sustained cannabis use was associated with improvements in pain intensity, pain interference, sleep quality, subjective cognitive function, and reaction times in the Stroop task, but no change in general quality of life was observed. High levels of cannabidiol (CBD) use during the two-week ad libitum use period was associated with steeper improvements in pain intensity and sleep quality. Participants reported improvements in pain intensity and increased feelings of subjective high after acute use. High levels of Δ9-tetrahydrocannabinol (THC) use during the acute administration appointment was associated with steeper increases in feelings of subjective high. Improvements in pain were associated with improvements in subjective cognitive function. Conclusions: This observational study is among the first of its kind to examine associations between legal market, palliative cannabis use, and subjective and objective outcomes among cancer patients. These early findings concerning pain intensity, sleep quality, and cognitive function can help to inform future, fully powered studies of this important topic (ClinicalTrials.gov identifier: NCT03617692).